The Slaw and the Slow Cooked: Culture and Barbecue in the Mid-South - Holtzman, Jon D. (Ethnobiology Letters, 2012)
Review of The Slaw and the Slow Cooked: Culture and Barbecue in the Mid-South. James R. Veteto and Edward M. Maclin, eds. 2011 Vanderbilt University Press, Nashville. Pp. 216 22.95 (paperback). ISBN 978-0826518019.